MEDIA SOSIAL DAN KRISIS MORAL GENERASI MUDA: TANTANGAN DAN PERAN PENDIDIKAN AGAMA ISLAM DI ERA GLOBAL - Fenindra Jailani; Hairil Anwar; Sapril (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article critically examines the role of Islamic Religious Education (PAI) in responding to the moral crisis among young generations triggered by the massive use of social media in the global era. Moral degradation phenomena such as free association, dissemination of negative content, and the weakening of religious values among adolescents are increasingly alarming with the rapid growth of digital platforms. This study employs a qualitative approach with library research method, analyzing relevant primary and secondary sources from Islamic education literature, educational psychology, and media studies. The findings indicate that PAI has strategic potential that has not been fully optimized in shaping the moral character of young generations through three main approaches: internalization of tawhid values, development of emotional-spiritual intelligence based on the Quran and Sunnah, and innovation of technology-based digital learning. This study argues that the challenge of social media should not merely be addressed through restriction, but through a transformation of PAI learning paradigms that are responsive, contextual, and oriented toward the formation of insan kamil (the perfect human being). The implications of this study are relevant for PAI curriculum development, teacher training, and national education policy.